CIRCADIAN VARIATION IN THE ONSET OF ACUTE MYOCARDIAL INFARCTION IN DIABETICS - Kumar, Suresh; Kumar, Naresh; Kumar, Haresh; Niazi, Rizwan Ahmed; Rashid, Muhammad Farhan (Journal of Ayub Medical College Abbottabad, 2018)
Background: It has been shown in previous studies there is circadian variation in the onset of acute myocardial infarction. The objective of this study was to evaluate the relation of circadian variation in onset of Acute Myocardial infarction in Diabetic subjects. Methods: This study was conducted at the Services Institute of Medical Sciences Lahore and Punjab Institute of Cardiology from January 2015 to February 2016. Hundred diabetic and 100 Non-diabetic patients with Myocardial infarction were included in the study. Among diabetics those were included in the study who had diabetes for ‰¥5 years. The time of onset of symptoms to determine the circadian rhythm was noted. In order to determine the frequency of acute myocardial infarction associated with circadian rhythm, 24 hours of the day were divided into four equal sections of 6 hours each. We noted time of onset of acute MI. Thereafter, patients were bracketed in their respective six-hour time periods. These six-hour periods were 0-6, 6:01-12, 12:01-18, and 18:01-24 hours. Result: In this study patients’ mean age was 59.16±13.81. Forty-two (71.2%) non-diabetic patients had acute myocardial infarction (AMI) during 6:00-12:00 hours whereas 17 (28.8%) diabetic patients presented with AMI during this time. Conclusion: Incidence of AMI is significantly increased in the morning 6:01-12:00 hours in non-diabetics. However, diabetic subjects did not show significant increased incidence of AMI during this time rather there was increased incidence of AMI during 0-6:00 hours. Keywords: Circadian variation; Myocardial infarction; Diabetes